(In)security in the family - Grabowiec, Anna (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
This article is an attempt to show the complexity of the domestic violence problem. The author presents in it the forms of violence against children as well as adult family members. Special attention was paid to the very often ignored kind of victimization, namely the children being witnesses of violence between their parents or between other children in the family. The article shows the scale of the domestic violence problem in the light of the empirical research done in Poland and confronted with foreign research results. Special attention was also paid to the situation of a child experiencing violence from his/her relatives.
Keywords: domestic violence; physical violence; psychological violence; sexual abuse; neglect